Lymphotropic therapy: history, achievments, outlook - Gariaeva N.А.; Zavgorodnii , I.G.; Garyaev , K.P. (Perm Federal Research Centre Journal, 2023)
In the article, the role of the Soviet, Russian and European schools of lymphologists is assessed in development of the lymphotropic therapy as a method of medical correction of structures and functions of lymphatic system. The influence of lymphotropic therapy on pathogenesis of infectious, degenerative, allergic, and autoimmune diseases in the context of morphology and physiology of the lymphatic system is described. The paper provides data on the effectiveness of lymphotropic therapy, describes local and systemic effects of lymphotropic therapy. Lymphotropic therapy is considered as an alternative way to deliver modified drug compositions to the lesion site via vascular (lymphatic) and extravascular (interstitial) transport. An overview of the implementation of lymphotropic therapy in various areas of clinical practice is given. In addition, the authors analyze the problems and prospects for further research on the application of lymphotropic therapy in Russia and abroad.